Financial Performance of Banten Province Before and During the Covid-19 Pandemic - Suci Rahmawati Prima (JFBA: Journal of Financial and Behavioural Accounting, 2022)
The government of Indonesia has taken several policies to reduce the State Revenue and Expenditure Budget as a consequence of the Covid-19 pandemic. This also affects the financial condition of local governments, including the province of Banten. This study aims to determine the financial performance of the Banten province in the pre-pandemic and during the pandemic which is reflected in the degree of fiscal decentralization, the effectiveness of local own-source revenue, degree of dependency, and independence. This research is a quantitative descriptive genre using secondary data from 2015-2021 sourced from reports on the results of financial audits from BPK-RI and The Central Bureau of Statistics of Banten. The method used in this research is financial ratio analysis and comparison of results. The results showed that the degree of fiscal decentralization of Banten province was in a very good category with effective PAD, the degree of regional independence was in a good category and the degree of dependence was low. The results of intra and inter-comparisons show that Banten's position in financial performance during the pandemic is in the very good category. This study recommends the need for commitment and consistency of local governments to continue to improve and maintain financial independence.